Two new centric diatoms (Bacillariophyta) from the sub-Antarctic region - van De Vijver, Bart; Houk, Václav (Phytotaxa, 2019)
During a survey of the limno-terrestrial diatom flora of the sub-Antarctic region, two unknown melosiroid diatom taxa were observed in several shaded, damp cave (moss and soil) samples from Heard Island and Ile de la Possession, the main island of the Crozet Archipelago. Comparison with already known species from the genus Melosira and the recently described genera Arcanodiscus, Angusticopula and Ferocia, resulted in the description of both new taxa based on detailed light and scanning electron microscopy. A first species was described as Ferocia subantarctica sp. nov. and can be distinguished based on its numerous, narrow girdle bands, relatively weakly domed valves, a limited number of well-developed spines and a rather large, hyaline central area. The second species, Arcanodiscus desmetianus Van de Vijver sp. nov., can be recognized based on its solitary frustules, a series of parallel ridges surrounding the mantle and a hyaline central area that is only less than 50% of the total valve diameter. Both taxa are morphologically and ecologically characterized and compared with all known melosiroid taxa worldwide.